Larval fish habitats in a mesoscale dipole eddy in the gulf of California. (September 2015) - Apango-Figueroa, Ethel; Sánchez-Velasco, Laura; Lavín, Miguel F.; Godínez, Victor M.; Barton, Eric D.
Abstract: The three-dimensional distribution of larval fish habitats in a mesoscale dipole eddy was analyzed in the Southern Gulf of California in July 2010. Detection of the characteristic mushroom-shape using chlorophyll and sea surface temperature satellite images was used to direct sampling of two transects across the structure with conductivity, temperature, depth casts and stratified oblique zooplankton hauls with opening-closing net. The latter sampled every 17 m layer down to the thermocline and every 50 m layer from the thermocline down to 200 m depth. Lowered Acoustic Doppler Current Profiler velocities revealed that the dipole structure persisted down to 800 m depth. The "cap" showed two opposite poles: one cyclonic with diameter 50 km, and the other anticyclonic with diameter 80 km. It had a vigorous central jet with speeds>25 cm/s. The Θ-S A properties were consistent with formation of the structure outside the Gulf of California in Tropical Surface and Subtropical Subsurface water masses. In this context, three larval fish habitats were statistically defined ( P <0.001). One habitat, located in the surface mixed layer ( 15 m depth), was characterized by the highest species richness, high abundance of the mesopelagic species Vinciguerria lucetia and the presence of epipelagic species like Auxis sp.; this habitat was correlated with the warm (24–25 °C) and oxygenated (4–5 mL/L) Tropical Surface Water. The other two larval fish habitats were defined below the thermocline (between 15 and 50 m depth) and comprised mainly by mesopelagic species. One of them occurred in the cyclonic pole and central jet zone with the highest larval abundance, dominated by Diogenichthys laternatus; the other habitat was located in the dipole margins, or zones of return flow, with the lowest larval abundance, characterized by Psenes sio and Bathylagoides wesethi, species frequent outside of the Gulf of California. These two habitats were correlated with cooler ( 13–22 °C) and hypoxic (0.03–1 mL/L) Subtropical Subsurface water masses. The results suggest that during the formation of the dipole, water masses dominated by different species were trapped, forming larval fish habitats. Highlights: For the first time, effects of a dipole eddy-pair on biological indicators are determined. The dipole demonstrably defined larval fish habitats with hydrographic boundaries. A larval habitat was associated with Tropical Surface Water in the surface of the dipole. Two habitats below the thermocline were associated with the cyclonic pole and its margin. Larval fish habitats in the dipole may persist while the mesoscale structure remains stable.